Analisis Faktor Bahaya dan Resiko Menggunakan Pendekatan HIRADC pada Produksi Pusat Keripik Tempe di Kota Malang - Aktul Hasanah, Annisa Mufi; Sulistyorini, Anita; Hanifah, Athiya Khansa; Nisa'iyah, Fitrotun; Saputri, Lorenza Arinda; Fatur Rohman, Muhammad Fajar; Risma Widyaningsih, Rosa Okta (Universitas Negeri Malang, 2024)
Abstract The tempe chips production center poses a risk to the health and safety of workers due to the production process not being completely safe and the lack of implementation of occupational health and safety standards. The method used in this research is descriptive observational with a focus on Job Safety Analysis (JSA) and Hazard Identifications, Risk Assessment and Risk Control (HIRADC). This research aims to evaluate risk factors that may occur during the tempeh chips production process. From observations and interviews with production workers, it is known that several production stages such as cutting tempeh, frying and packaging face various potential risks. The analysis results show that there is a moderate to high level of risk, including dangers such as slippery floors, hot oil splashes and gas leaks. Recommended preventive measures include changes in work posture, use of personal protective equipment (PPE), as well as increased ventilation and separation of work spaces. It is hoped that the results of this research can contribute to improving occupational safety and health in the tempeh chips industry, by reducing the risk of accidents and occupational diseases.